Peritoneal fibrosis: from pathophysiological mechanism to medicine - Kang, Yingxi; Liu, Yuan; Fu, Ping; Ma, Liang (Frontiers in Physiology, 2024)
Peritoneal dialysis (PD) is currently one of the effective methods for treating end-stage renal disease (ESRD). However, long-term exposure to high concentration glucose in peritoneal dialysis environment could lead to peritoneal fibrosis (PF), impaired peritoneal filtration function, decreased peritoneal dialysis efficiency, and even withdrawal from peritoneal dialysis in patients. Considerable evidence suggests that peritoneal fibrosis after peritoneal dialysis is related to crucial factors such as mesothelial-to-mesenchymal transition (MMT), inflammatory response, and angiogenesis, etc. In our review, we summarize the pathophysiological mechanisms and further illustrate the future strategies against PF.